Empathy through reflection: Exploring the impact of reflective practices on Vietnamese tertiary EFL teachers' empathy development - Thuy, Pham Trut; Thao, Le Thanh; Thuy, Tran Thi (Diksi, 2024)
This study investigates the role of self-reflection in enhancing empathy among Vietnamese tertiary English as a Foreign Language (EFL) teachers. Adopting a narrative inquiry approach, the research explores the experiences and perceptions of nine EFL teachers from various career stages in two Vietnamese institutions. The theoretical framework is grounded in the theory of reflective practice and transformative learning theories, offering a comprehensive lens to examine the interplay between reflective practices and empathy development in teaching. Through semi-structured interviews, the study uncovers several key themes: enhanced empathetic understanding through reflective practice, the facilitation of cross-cultural sensitivity, the intersection of self-reflection and empathy in pedagogical evolution, the enhancement of emotional intelligence, and the bridging of cultural and emotional gaps through reflective empathy. These findings suggest that reflective practices are instrumental in developing a deeper sense of empathy, which positively impacts teaching approaches, cultural awareness, and emotional intelligence.